Kajian Teknis Penyangga Baja Three Piece Sets dan Five Piece Sets Pada Lubang Bukaan Tambang Batubara Bawah Tanah Pit Central Barat Di PT. Allied Indo Coal Jaya - Redy Pratama; Raimon Kopa (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract. Underground mining require system, design, and mine support capacity planning. The purpose of this research is to study technical part of the use of three piece and five piece steel support at Central Barat PIT underground mine in PT. Allied Indo Coal Jaya. The idea is comparing maximum moment of three pieces structured i-beam with five pieces structured support which almost has arches shape in the same area in the underground mine. This research method is quantitative, which mean getting numeric data, calculating load that apply on mine support, calculating mass of potential rock fall using appropriate empiric equation approach to measure the load that apply on these underground mine support. The research result shows that maximum moment on three pieces bar (BC) = 17.25 kN m and five pieces bar (CD) = 3.99 kN m. Five piece support take less moment compared to three pieces support, due to smaller surface and it distribute the load to each bar. At the same area, five pieces use smaller steel size 80 mm x 42 mm and 5,94 kg/m compared to three pieces with 140 mm x 66 mm and 14,37 kg/m size of steel. This cause the cost for steel use for five pieces support is more economical than three pieces supportKey words; steel support, underground mine, three piece, five piece, and maximum moment